Exploring Curated Conformational Ensembles of Intrinsically Disordered Proteins in the Protein Ensemble Database. Issue 7 (12th July 2021) - Quaglia, Federica; Lazar, Tamas; Hatos, András; Tompa, Peter; Piovesan, Damiano; Tosatto, Silvio C. E.
Abstract: The Protein Ensemble Database (PED; https://proteinensemble.org/ ) is the major repository of conformational ensembles of intrinsically disordered proteins (IDPs). Conformational ensembles of IDPs are primarily provided by their authors or occasionally collected from literature, and are subsequently deposited in PED along with the corresponding structured, manually curated metadata. The modeling of conformational ensembles usually relies on experimental data from small‐angle X‐ray scattering (SAXS), fluorescence resonance energy transfer (FRET), NMR spectroscopy, and molecular dynamics (MD) simulations, or a combination of these techniques. The growing number of scientific studies based on these data, along with the astounding and swift progress in the field of protein intrinsic disorder, has required a significant update and upgrade of PED, first published in 2014. To this end, the database was entirely renewed in 2020 and now has a dedicated team of biocurators providing manually curated descriptions of the methods and conditions applied to generate the conformational ensembles and for checking consistency of the data. Here, we present a detailed description on how to explore PED with its protein pages and experimental pages, and how to interpret entries of conformational ensembles. We describe how to efficiently search conformational ensembles deposited in PED by means of its web interface and API. We demonstrate how to make sense of the PED protein page and its associated experimental entry pages with reference to the yeast Sic1 use case. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. [Correction added on May 17, 2022, after first online publication: CRUI‐CARE funding statement has been added.] Basic Protocol 1 : Performing a search in PED Support Protocol 1 : Programmatic access with the PED API Basic Protocol 2 : Interpreting the protein page and the experimental entry page—the Sic1 use case Support Protocol 2 : Downloading options Support Protocol 3 : Understanding the validation report—the Sic1 use case Basic Protocol 3 : Submitting new conformational ensembles to PED Basic Protocol 4 : Providing feedback in PED